Lifestyle intervention as a treatment for obesity in school-age-children in Celaya, Guanajuato: An experimental study - Nicolas Padilla-Raygoza; Rosalina Diaz-Guerrero; Ma. Laura Ruiz-Paloalto (University Library System, University of Pittsburgh, 2013)
Introduction: Obesity is a risk factor in chronic diseases, and its frequency among children in Mexico is increasing. Objective: To determine the effect of lifestyle intervention as a treatment for obesity in school-age-children from Celaya, Mexico. Methodology: For this experimental study, four schools were randomly selected. Children and parents participated voluntarily and signed consent forms. Two schools were chosen as the experimental group and the other two formed the control group. Age, gender, weight, height, BMI and blood pressure were recorded for each participant. Intervention: Children and parents were asked to walk in their schools for 30 minutes a day Monday through Friday and to attend 8 instructional sessions over a period of four months dedicated to the selection and preparation of meals. Statistical Analysis: The OR and 95% CI were calculated to determine the effect of the intervention; a Z-test for two proportions for overweight and obesity in the control and experimental groups were carried out for comparison. Results: 157 children were included in the experimental group and 144 in the control group. To compare the proportions of the overweight and the obese between the groups, a Z-test = - 0.36 (p-value 0.72) were obtained showing no effect of the intervention in lifestyle; OR =1.09, 95% CI (0.67, 1.77). It was adjusted according to the attendance to the sessions resulting in an OR = 2.00, 95% CI (0.69, 5.77), demonstrating that not attending the sessions was a confounder. Conclusions: Intervention in lifestyle should be measured over a longer period of time in order to determine what effects it may have on changes in body mass index.